OBTAINING A SYMBIOTIC DRINK FROM FRESH CHEESE SERUM - Ricaurte Ortiz, Paul (2017)
In the research it was possible to obtain a symbiotic drink, starting from whey, which was subjected to a pasteurization followed by a protein separation using the isoelectric point of the serum, thus precipitating the β - lactoglobulin and separating it by transfer, using two types of Ferments 1. (YO-MIXTM 495), and 2. (LAT BY 9R), these ferments are inoculated at 42 and 37 ° C. Maintaining these temperatures during 3:30 and 6:00 hours respectively. The incorporation of inulin and oligofructose, is 0.85%, thus acquiring a percentage of 0.58% of oligofructose in the lacto serum drink. A bifactorial design was applied: A is the percentage of whey (100, 75 and 50) and B is the yeast, with a total of 18 treatments, the analyzes were:protein, solids, lactic acid bacteria, Lactic acid, coliforms. Statistical results show that the best treatment for serum lactobacillus is 100% A1B2 and LAT BY 9R